Anatomia floral de espécies de Bulbophyllum sect. Micranthae (Orchidaceae, Asparagales) - Rabelo, Paula Maldonado [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Bulbophyllum, which comprises 1876 species, is considered the second largest genus of angiosperms, with a pantropical distribution. The morphological and anatomical floral studies in the genus are incipient, with data restricted to the gynostemium and lip of some species. Based on molecular data, six sections were recognized within Bulbophyllum at the Neotropics, amongst them Bulbophyllum sect. Micranthae, which comprises 12 species distributed in central South America. We aimed to study the floral anatomy of six species of Bulbophyllum sect. Micranthae, in order to determine useful characters to differentiate them and contribute to the anatomical characterization of the section as a whole. Floral anatomy was assessed through usual techniques of light microscopy. The data found here for B. adiamantinum, B. chloroglossum, B. epiphytum, B. mentosum, B. micranthum and B. rupicolum allowed to identificate the presence of glandular trichomes and the possible presence of a secretory region on the lip, which might produce substances used as a reward to pollinators. The most significant anatomical characters to the species characterization were the shape and ornamentation of the outer periclinal walls of the epidermal cells, as well as the number of vascular bundles in dorsal and lateral sepals and at the lip. The data also allowed the differentiation between B. epiphytum and B. rupicolum, species very similar in morphology and phylogenetically related. Besides that, the data also allowed the discussion regarding the maintenance of B. mentosum within the section: although its inclusion is supported by molecular studies, the anatomical data here presented shows greater differences compared to the other species, not supporting its maintenance in Bulbophyllum sect. Micranthae

Bulbophyllum, com 1876 espécies, é considerado o segundo maior gênero de angiospermas, com distribuição pantropical. Os estudos morfológicos e anatômicos florais no gênero são incipientes, com dados de ginostêmio e labelo de algumas espécies. Atualmente, são propostas seis seções para o gênero na região neotropical, dentre elas Bulbophyllum sect. Micranthae, que compreende 12 espécies, distribuídas na região central da América do Sul. O presente trabalho teve por objetivo o estudo anatômico das peças florais de seis espécies de Bulbophyllum sect. Micranthae, de modo a levantar caracteres que auxiliem na diferenciação das mesmas e que possam contribuir para o conhecimento anatômico e caracterização da seção. Para o levantamento dos caracteres anatômicos foram utilizadas técnicas usuais de microscopia de luz, com documentação com projeção da escala micrométrica. Os resultados aqui obtidos para B. adiamantinum, B. chloroglossum, B. epiphytum, B. mentosum, B. micranthum e B. rupicolum permitiram identificar a presença de tricomas e evidências de regiões produtoras de substâncias no labelo, que podem servir como recompensa a polinizadores. Os caracteres anatômicos que se mostraram mais significativos na caracterização das espécies foram o formato e a ornamentação das paredes periclinais externas das células epidérmicas das peças florais, bem como o número de feixes vasculares nas sépalas, dorsal e lateral, e na porção distal do labelo. As características levantadas permitem a diferenciação principalmente entre B. epiphytum e B. rupicolum, espécies muito semelhantes morfologicamente e filogeneticamente relacionadas, além de permitirem aprofundar a discussão a respeito da manutenção ou exclusão de B. mentosum na seção, uma vez que, apesar de dados moleculares suportarem sua inclusão, os dados aqui obtidos demonstram grandes diferenças anatômicas em comparação às demais espécies, não...
Keywords: Anatomia vegetal; Orquídea; Flores - Anatomia